2016
DOI: 10.1177/0300060516666398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and biological markers of lung cancer-associated stroke

Abstract: ObjectiveTo identify the unique clinical features and biological markers of lung cancer-associated stroke.MethodsWe recruited 102 patients with lung cancer plus stroke, 102 with lung cancer, and 102 with stroke. Detailed information was analysed and compared among groups.ResultsThe groups were age-matched. Patients with lung cancer plus stroke showed multiple lesions involving multiple cerebral artery territories on magnetic resonance imaging, compared with stroke-alone patients. These patients also had a poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…In a 2014 study, patients with active cancer and ischemic stroke tended to demonstrate higher CRP and D-dimers, more frequent cryptogenic strokes and patterns of multiple lesions, and among those patients, higher CRP and D-dimer levels were associated with a cryptogenic mechanism and multiple lesion patterns (17). In agreement with that study, Xie et al analyzed data from patients with lung cancer and came to the conclusion that high D-Dimers, alongside CA125 and CA199, were independent risk factors for lung-cancer-associated stroke (146). In a different study, lung cancer was also associated with high CRP levels (7).…”
Section: Detection Of a Cancer-associated Strokesupporting
confidence: 52%
See 3 more Smart Citations
“…In a 2014 study, patients with active cancer and ischemic stroke tended to demonstrate higher CRP and D-dimers, more frequent cryptogenic strokes and patterns of multiple lesions, and among those patients, higher CRP and D-dimer levels were associated with a cryptogenic mechanism and multiple lesion patterns (17). In agreement with that study, Xie et al analyzed data from patients with lung cancer and came to the conclusion that high D-Dimers, alongside CA125 and CA199, were independent risk factors for lung-cancer-associated stroke (146). In a different study, lung cancer was also associated with high CRP levels (7).…”
Section: Detection Of a Cancer-associated Strokesupporting
confidence: 52%
“…Karlińska et al (2015) also noted that patients with stroke with an active cancer tended to present lower hematocrit levels, higher serum CRP levels, and a higher erythrocyte sedimentation rate when compared to cancer-free stroke patients (27). Several other studies have also reported elevated D-Dimers levels in cancer patients (7,19,146,147). Taking into consideration the significance D-Dimers seem to have in the diagnosis of cancer-related stroke, Guo et al (2014) used D-Dimers of ≥0.55 mg/l, and multiple territory infarctions, as criteria for the development of a clinically meaningful test for cancer-associated stroke.…”
Section: Detection Of a Cancer-associated Strokementioning
confidence: 73%
See 2 more Smart Citations
“…Some serum markers, such as elevated serum D-dimer, CA125, and fibrinogen levels were found to be associated with hypercoagulability and are independent risk factors for CRIS. 5,6,8 In the present study, we found that elevated serum D-dimer and CEA levels and an increased PLT count were independent risk factors for BCRIS. There is an increasing amount of evidence for elevated serum D-dimer levels in stroke patients with active cancer.…”
Section: Discussionsupporting
confidence: 54%